Malta : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper assesses the marginal impact of promoting inclusive growth in Malta. The paper uses a multi-country simulation model, the IMF's Flexible System of Global Models calibrated for Malta, is used to analyze the macroeconomic impacts of ongoing and potential future reforms. Three different policies are analyzed, namely: increasing childcare and after care benefits; extending working lives; and upskilling the labor force. The model shows that the reduction of absolute poverty has been accompanied by rising inequality. The simulation evaluates the macroeconomic impact of introducing free childcare, which is the actual government policy since 2015. Simulations show that policies that are primarily aimed at improving social inclusion also end up boosting potential output, thereby mitigating the fiscal cost of such policies in the long term. Recent declines in poverty rate can partly be ascribed to the cycle, however, recent structural reforms likely have had a significant impact on growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet